The exploration of the meaning of body part terms in Batak Toba language: Natural Semantic Metalanguage approach - Manurung, Yayuk Hayulina; Mulyadi, Mulyadi; Oktavianus; Gustianingsih (Research Journal in Advanced Humanities, 2025)
Since everyone shares a common physiology, the body is an obvious place to look for universally shared aspects of meaning. Cross-linguistic studies, however, show that there is a great deal of variation in the expansion of terms for human body parts. This study explores the construction of body parts terms on Batak Toba by employing a natural semantic metalanguage (NSM) analysis. This research was done through qualitative descriptive approach within the framework of Natural Semantic Metalanguage (NSM) analysis. Data collection involved interviews with native speakers, a review of linguistic literature, and comparison with existing semantic studies. The results reveal that there is no terminology for Adam’s apple and some terms refer to different parts of the body even though their location is close to each other such as hurrum is for temple, cheeks, and jaw and siholtingon is for hips and waist. The construction of the body parts named in Batak Toba dominantly is formed by the shape, location, and function of the body parts themselves. This finding proves how speakers of the Batak Toba language had considered very considerably in forming the body parts names long before the presence study of the semantics of body parts. Further research should be conducted to preserve the traditional language for local wisdom.